2000
DOI: 10.1016/s1387-6473(00)00021-x
|View full text |Cite
|
Sign up to set email alerts
|

Secondary stars in CVs: the theoretical perspective

Abstract: We apply the new generation of theoretical models of low-mass stars to secondaries in CVs, focussing on systems above the period gap. The models confirm that the spectral type should be a good indicator of the donor mass. The orbital period-spectral type diagram can potentially constrain the long-term mean mass transfer rate. A transfer rate that increases with decreasing period is most easily reconciled with the observational data.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 22 publications
(18 reference statements)
3
24
0
1
Order By: Relevance
“…Silber et al (1994) found that the optical spectrum of V2301 Oph taken at mid‐eclipse was most similar to an M6 V spectral type. Based on the theoretical models of Kolb & Baraffe (2000), such a spectral type implies a secondary star mass, M 2 = 0.10 M ⊙ . The same models also predict the spectral type of the secondary star as a function of orbital period.…”
Section: The Light Curvesmentioning
confidence: 88%
See 1 more Smart Citation
“…Silber et al (1994) found that the optical spectrum of V2301 Oph taken at mid‐eclipse was most similar to an M6 V spectral type. Based on the theoretical models of Kolb & Baraffe (2000), such a spectral type implies a secondary star mass, M 2 = 0.10 M ⊙ . The same models also predict the spectral type of the secondary star as a function of orbital period.…”
Section: The Light Curvesmentioning
confidence: 88%
“…The same models also predict the spectral type of the secondary star as a function of orbital period. For an orbital period appropriate to V2301 Oph (113 min) the models predict a secondary of spectral type of ∼M4.5 (Baraffe & Kolb 2000), which implies M 2 = 0.15 M ⊙ (Kolb & Baraffe 2000). For M 2 = 0.10 and 0.15 M ⊙ and q = 0.15 (Reynolds et al 2005), this implies M 1 = 0.67 and 1.0 M ⊙ , respectively.…”
Section: The Light Curvesmentioning
confidence: 98%
“…In the case of an X-ray heated star, the radius can be increased by a factor as large as two (Hameury et al 1993), while an evolved main sequence star scenario also implies a significantly larger stellar radius (Kolb & Baraffe 2000) (see our cautionary statement in Sect. 3.4).…”
Section: The Radius Of the Secondarymentioning
confidence: 99%
“…These two relations, using the improved orbital period, give M 2 = 1.14 M ⊙ and M 2 = 1.07 M ⊙ , respectively. The spectral types labelled on the left‐hand side of the diagram correspond to the zero‐age main sequence (ZAMS) stellar models discussed by Kolb & Baraffe (2000), while those shown on the right‐hand side correspond to evolved stars that are still within the main‐sequence band (see Kolb & Baraffe 2000 for detailed explanations). Points in the white area are then within these limits as we expect that the primary star will not exceed the Chandrasekhar limit, and that the secondary star will not be on the MS (Echevarría 1983; Beuermann et al 1998).…”
Section: The M1–m2 Diagrammentioning
confidence: 99%